Teoria de Dirac modificada no Modelo Padrão Estendido não-mínimo. - REIS, João Alfíeres Andrade de Simões dos (2017)
For the recent years, there has been a growing interest in Lorentz-violating theories. Studies have been carried out addressing the inclusion of Lorentz-violating terms into the Standard Model (SM). This has led to the development of the Standard Model Extension (SME), which is a framework containing modifications that are power-counting renormalizable and consistent with the gauge structure of the SM. More recently, a nonminimal version of the SME was developed for the photon, neutrino, and fermion sector additionally including higher-derivative terms. One of the new properties of this nonminimal version is the lost of renormalizability. In this work, we study the main aspects of a modified Dirac theory in the nonminimal Standard-Model Extension. We focus on two types of operators namely, pseudovector and two-tensor operators. These two operators display an unusual property; they break the degeneracy of spin. This new property becomes manifest in providing two di erent dispersion relations, one for each spin projection. To solve the Dirac equation modified by those operators, we introduce a new method that was suggested by Kostelecký and Mewes in a recent research paper. This method allows to block-diagonalizing the modified Dirac equation and, thus, permits us to obtain the spinors. The objectives of the current work are as follows. First, we will review the main concepts for understanding the SME. Second, we will introduce how to extend the minimal fermion sector to the nonminimal one. Third, we will describe the method that block-diagonalizes the modified Dirac equation and we will compute the field equations. And,finally, we will get the exact dispersion relations and the spinor solutions for operators of arbitrary mass dimension.